EVALUASI IMPLEMENTASI KEBIJAKAN OTONOMI PENDIDIKAN DARI DINAS PENDIDIKAN KABUPATEN/KOTA KE DINAS PENDIDIKAN PROPINSI KALIMANTAN TIMUR - Sjachruddin M. Seman; Husainie Usman; Johansyah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2020)
The objectives of the research are to: (1) find out the effectiveness of the implementation of education autonomy policy from regency / city to province; (2) to know the effectiveness of the realization of education budget; (3) to know the effectiveness of quality improvement of education quality; (4) to know politicization; And (5) finding new strategies for implementing education autonomy policies. The study used the Tyler model evaluation study. Level of effectiveness using percentages. Qualitative data were analyzed with McMilland model. The validity of qualitative data uses credibility, dependability, transferability, and confirmability.The study concluded: (1) the implementation of education policy autonomy is about 50% (quite effective), qualitatively ineffective; (2) the realization of the education budget is 25% (not effective) and also qualitatively ineffective; (3) teacher quality improvement 65.30% (effective), qualitatively ineffective; (4) teacher politicization hampers the professionalism and career development of teachers, shifts the politicization of teachers from districts / municipalities to the politics of what, when, and how to get something, no true friend of true interest, art of possibility, way; (5) the new strategy for streamlining the implementation of education autonomy policy is 8K in bebaya